A Literary-Psychological Exploration Of Jordan Belfort’s Character In The Wolf Of Wall Street - Zachary, Ferraz Aditya; Zaidan, Muhammad Ariq; Rosalinah, Yanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the portrayal and development of Jordan Belfort’s character in The Wolf of Wall Street (2013), focusing on how the film constructs him as a literary figure shaped by ambition, greed, and complex moral tension. The research analyzes the narrative techniques used to depict Belfort’s transformation, beginning with his initial aspirations as a young stockbroker, followed by his rapid rise to power, and culminating in his moral downfall. Key scenes are explored to highlight moments that reveal shifts in his values, behavior, and psychological state, illustrating the progression from ambition-driven success to ethically corrupt excess. The study further investigates the internal and external conflicts that define Belfort’s character arc. Internally, Belfort struggles with impulses related to addiction, desire for dominance, and a deteriorating moral compass. Externally, he faces pressures from corporate culture, peer influence, and the legal system, all of which shape his decisions and accelerate his descent. These conflicts work together to reinforce the film’s central themes, including the seduction of wealth, the fragility of moral integrity, and the consequences of unrestrained ambition. The findings reveal that Belfort’s psychological turmoil and interactions with his environment serve as a narrative device through which the film critiques the culture of greed and ethical corruption within the financial world. Through its characterization and storyline, the film offers a powerful commentary on how unchecked ambition can lead to self-destruction, harming both the individual and those around him.